Proteostasis Strategies for Restoring α(1)-Antitrypsin Deficiency - Bouchecareilh, Marion (American Thoracic Society, 2010)
The function of the human proteome is defined by the proteostasis network (PN) (Science 2008;319:916; Science 2010;329:766), a biological system that generates, protects, and, where necessary, degrades a protein to optimize the cell, tissue, and organismal response to diet, stress, and aging. Numerous human diseases result from the failure of proteins to fold properly in response to mutation, disrupting the proteome. In the case of the exocytic pathway, this includes proteostasis components that direct folding, and export of proteins from the endoplasmic reticulum (ER). Included here are serpin deficiencies, a class of related diseases that result in a significant reduction of secretion of serine proteinase inhibitors from the liver into serum. In response to misfolding, variants of the serine protease α(1)-antitrypsin (α1AT) fail to exit the ER and are targeted for either ER-associated degradation or autophagic pathways. The challenge for developing α1AT deficiency therapeutics is to understand the PN pathways involved in folding and export. Herein, we review the role of the PN in managing the protein fold and function during synthesis in the ER and trafficking to the cell surface or extracellular space. We highlight the role of the proteostasis boundary to define the operation of the proteome (Annu Rev Biochem 2009;78:959). We discuss how manipulation of folding energetics or the PN by pharmacological intervention could provide multiple routes for restoration of variant α1AT function to the benefit of human health.